“THE CREATURE ITSELF IS NASTY, BUT NOTHING REALLY COMPARES TO THE BUILDING OF DREAD BEFORE YOU EVER GET TO IT”: ONLINE PLAYER AND DEVELOPER COMMENTARY ON FEMALE MONSTROSITY IN VIDEO GAMES - Stang, Sarah Marie (AoIR Selected Papers of Internet Research, 2021)
Gender representation in video games has long been a fraught topic of discussion within online gaming communities. In game scholarship, analysis of the usually harmful tropes and trends of female representation has resulted in countless studies demonstrating that video games are often a regressive medium in terms of representation, privileging heterosexual white male subjectivities and erasing, marginalizing, or even vilifying anyone outside of that specific demographic. These conversations and scholarly studies tend to focus on the representation of human women, especially as victimized damsels-in-distress. Considerably less work has been done to analyse the portrayal of villainous and monstrous nonhuman women in games, even though countless science fiction, fantasy, and horror games feature these kinds of characters. Many of these games utilize harmful tropes and design practices related to female villainy and monstrosity, thereby reinforcing misogynistic ideologies. With the understanding that gender representations in games can have deep cultural ramifications, especially as they intersect with representations of race, sexuality, queerness, body size, disability, mental illness, and age, this paper examines online player and developer discourse regarding female-coded monsters from a selection of commercially successful “AAA” video games. The intent of this project is to contribute to ongoing scholarship on monstrosity in games by looking at how developers explain and justify their design processes in online interviews and forum posts and how players/fans articulate their attitudes towards and reception of these monstrous creatures.